The influence of different ways of training on development of practical skills in performing parenteral therapy in full-time first year nursing students - Ana Marija Hošnjak; Snježana Čukljek; Sanja Ledinski Fičko; Martina Smrekar (University of Ostrava, 2019)
Aim: This study aimed to determine how teacher demonstrations and video content affect the development of practical skills in the administration of intravenous therapy by nursing undergraduate students. Design: Prospective randomized trial. Methods: The study included 48 students in their first year of nursing studies, divided into two groups. In the first phase, the group of "video students" (n = 22) were trained to perform practical intravenous therapy skills by video demonstration, while the second group of "demonstration students" (n = 26) were instructed by live classroom demonstration. Both groups joined the second phase of the study after an interval of one week, when they were tested with the Objective Structured Clinical Examination (OSCE) for intravenous therapy. Results: Statistically significant differences were determined between the "video student" and "demonstration student" groups at a significance level of 0.05 (p < 0.05) for certain OSCE components. Conclusion: Pre-recorded video content is not an adequate substitute for live demonstration by teachers for mastering practical skills.